Testing the Effect of Grape Seed Extract (Vitis Vinifera L) on the Healing Process of Cut Wounds in Wistar White Rats - Rizali, Siska Saidi; Leslie, William; Chairul, Muhammad; Edlin, Edlin (Poltekkes Kemenkes Palu, 2024)
Daily actions cause wounds. Normal and abnormal wounds generate inflammation. Grape (Vitis vinifera l) possesses antioxidant and wound-healing properties. The research aims to test grape seed extract’s ability to heal cuts in white Wistar rats. The study is conducted solely on white Wistar rats. The type of research used was lab-experimental quantitative research with SPSS data. The study sample consisted of white Wistar rats (Rattus norvegicus). In this trial, grape seed extract was given at 50, 100, 150, and 200 mg/kg BW. Animals were sliced at 2 cm length with a depth of ± 2 mm to the dermis layer and treated according to their group. Grape seed extract cream healed mice-cut wounds. On the 14th day, group P0 had 72.3% wound healing, group P1 84.3%, group P2 94%, group P3 93.9%, and group P4 100%. Thus, group P4 healed faster than P0, P1, P2, and P3. Grape seed extract cream accelerates skin regeneration and stimulates fibroblasts more than base cream, according to wound healing percentages. Grape seed extract at 200 mg/kgBW accelerated wound healing more than other treatments. The entire treatment group demonstrated considerable normalcy with a 0.200 > 0.05 score. Four homogenous test groups had a significance value of 0.200 > 0.05. The one-way ANOVA test yielded a significance value of 0.000 < 0.05. The research concluded that grape seed extract contains saponins, alkaloids, steroids, and flavonoids that may serve as anti-inflammatory agents and antioxidants to inhibit free radicals and speed wound healing in rats.